HUBUNGAN PENGETAHUAN DAN SIKAP IBU MENGENAI STUNTING DENGAN KEJADIAN STUNTING DI DESA TIGA, SUSUT, BANGLI - Luh Dila Ayu Paramita; Ni Luh Putu Shinta Devi; Putu Oka Yuli Nurhesti (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2021)
Stunting is one of global health problem which is not yet could be prevented especially in Indonesia where the stunting prevalention considered higher than other developing countries. Stunting on infants will bring negative impact if not countermeasured immediately. Fundamentally, life sustainability and health condition of an infant depend on the health condition of the mother. Mother's knowledge and attitude influence on how she takes care of her infants. This study aimed to find the relation of knowledge and attitude toward stunting with the occurance of stunting at Tiga Village, Susut, Bangli. This study used the descriptive correlational with cross sectional approach method. Samples were taken from Tiga Village, Susut, Bangli using simple random sampling method with the result that 107 samples. Based on the results of this study there were 77 infants (72%) who suffered from stunting. Mostly, the mothers were categorized as poor knowledge which was consisted of 67 mothers (62,2%). However, the attitudes were categorized as good which consisted of 78 mothers (72,9%). The further analysis found that there were weak relation and negative pattern between mother's knowledge and attitude toward stunting with stunting occurences. The significance value (p) of knowledge was 0.038 and of attitude was 0.011. Its expected the local health authorities (puskesmas) could increase their role in assessing and planning the health programs, especially to stunting prevention.